Introduction - Miichi, Ken; Farouk, Omar (Palgrave Macmillan, 2014)
Islam and Muslims in Southeast Asia have often been described using two sets of very contradictory terms. On the one hand, Islam in the region is imagined as being Sufistic, syncretistic and localized, and Southeast Asian Muslims are thought to be very different from their counterparts in the Middle East, who are considered to be orthodox and 'fanatical'. On the other hand, after the 9/11 attacks and especially after the October 2002 Bali bombing in Indonesia, the danger of radical Islam was emphasized and Southeast Asia suddenly became the 'second front' in the global'war on terrorism' (Conboy 2006). Some Muslims in Southeast Asia themselves shared this concern and even warned of the influences of 'transnational' Islamic movements.